The impact of Otago exercise programme on the prevention of falls in older adult: A systematic review - Yang, Yi; Wang, Kun; Liu, Hengxu; Qu, Jiawei; Wang, Yan; Chen, Peijie; Zhang, TingRan; Luo, Jiong (Frontiers in Public Health, 2022)
Objective To improve the quality of life of older adult in their later years, by increasing the physical activity participation of older adult, the occurrence of falls accident scores in older adult can be prevented. This paper comprehensively summarizes the origin, development, participation forms, and fitness effects of the Otago exercise program (OEP). Methods Using PubMed, web of science, CNKI, dimensional spectrum, and other databases, search for research papers from 2005 to April 2021 by using keywords such as Otago project exercise; aged, Fall; Cognitive function, Balance ability, Lower limb strength, Fall efficiency, and so on. PEDro Scale was used to check the quality of the literatures. Results A total of 34 papers were included after searching for kinds of literature related to the subject of this paper and after careful review by researchers. Conclusions Otago exercise programme is beneficial to improve the cognitive function of older adult, enhance their lower limb muscle strength and dynamic and static balance ability, and then improve the gait stability and posture control ability of older adult, which has significant positive benefits for the prevention of falls in older adult. OEP is helpful to improve the falling efficiency of older adult, help older adult overcome the fear of falling, and form a positive emotion of “exercise improves exercise,” to reduce the harm caused by sedentary behavior and the incidence of depression and improve their subjective wellbeing. Although OEP has significant positive effects on improving the health and physical fitness of older adult, preventing falls, and restoring clinical function, the corresponding neural mechanism for preventing falls is not very clear. At the same time, how OEP can be combined with emerging technologies to maximize its benefits needs to be further discussed in the future.